Determination of priority groups of indicators for threats identification to the financial security of insurance market - Achkasova, Svitlana (Technology audit and production reserves, 2017)
The object of research is economic processes in insurance market of Ukraine. Generally there is no methodology for financial security assessment of the individual insurer and the insurance market in Ukraine, approved within the regulatory impact and determining financial security is not considered that hinders the practice of providing threats identification. To achieve the objectives author used the following methods: analysis and synthesis, logic synthesis, hierarchy analysis method. Methodological basis of the study is insurance theory and insurance concepts. As a result the aim of research was achieved, namely the priority groups of indicators for threats identification to the financial security of the insurance market are identified. Using the hierarchy analysis method, the priority groups of indicators for assessing the financial security of the insurance market are defined. The highest priority received a group of indicators that characterize assets charter and equity capital (0.588), followed by a group of indicators characterizing the insurance market regarding macroeconomic development of the country, a group of indicators application of prudential and regulatory impact on the insurance market and a group of indicators characterizing insurance activities of insurance companies in the insurance market.